2009
DOI: 10.1029/2008ja013896
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric zonal velocities at conjugate points over Brazil during the COPEX campaign: Experimental observations and theoretical validations

Abstract: [1] We analyze in detail the zonal velocities of large-scale ionospheric plasma depletions over two conjugate stations inferred from OI 630 nm airglow all-sky images obtained during the Conjugate Point Equatorial Experiment (COPEX) campaign carried out in Brazil between October and November 2002. The conjugate stations were Boa Vista (BV) (geogr. 2.8N, 60.7W, dip angle 22.0°N) and Campo Grande (CG) (geogr. 20.5S, 54.7W, dip angle 22.32°S). Over Campo Grande, the zonal velocities were measured also by a system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 102 publications
(155 reference statements)
10
66
0
Order By: Relevance
“…Measurements in the Brazilian equatorial region during the COPEX campaign showed larger nighttime eastward drifts observed with the GPS technique than inferred from airglow observations (Sobral et al 2009). Simultaneous observations with these two techniques also provided information on the early night shear in the zonal plasma drift between the heights of the airglow and the GPS scintillation layers.…”
Section: Longitudinal Variation Of Equatorial Electric Fields and Plamentioning
confidence: 95%
See 1 more Smart Citation
“…Measurements in the Brazilian equatorial region during the COPEX campaign showed larger nighttime eastward drifts observed with the GPS technique than inferred from airglow observations (Sobral et al 2009). Simultaneous observations with these two techniques also provided information on the early night shear in the zonal plasma drift between the heights of the airglow and the GPS scintillation layers.…”
Section: Longitudinal Variation Of Equatorial Electric Fields and Plamentioning
confidence: 95%
“…Ground-based optical and spaced GPS observations have extensively been used to measure nighttime zonal drifts of equatorial plasma depletions over Brazil (e.g., Sobral et al 1999Sobral et al , 2009Terra et al 2004). Measurements in the Brazilian equatorial region during the COPEX campaign showed larger nighttime eastward drifts observed with the GPS technique than inferred from airglow observations (Sobral et al 2009).…”
Section: Longitudinal Variation Of Equatorial Electric Fields and Plamentioning
confidence: 98%
“…This aspect is also noted by few other investigators. Sobral et al (2009) reported that a tendency of the zonal velocities of EPBs to increase almost linearly with increasing solar flux units. The thermospheric zonal wind is responsible for the motion of EPBs.…”
Section: Discussionmentioning
confidence: 99%
“…(2013), and the authors observed a slower rate of increase in F10.7 in comparison to the increase in the EUV flux for high solar flux values, which might explain the nonlinearity feature depicted here in the plot of V zonal versus the F10.7 index. The solar flux effects on irregularity zonal velocities have also been studied by Sobral et al (2009) based on the formulations presented by Haerendel et al (1992) and Eccles (1998). They discussed the fact that around solar maximum years the magnitude of the thermospheric zonal wind velocities tends to be larger owing to an enhanced solar thermal tide.…”
Section: Ionospheric Irregularity Zonal Drift Velocitiesmentioning
confidence: 99%